Correlation between immune-related adverse events and efficacy in non-small cell lung cancer treated with nivolumab. (January 2018) - Sato, Koichi; Akamatsu, Hiroaki; Murakami, Eriko; Sasaki, Seigo; Kanai, Kuninobu; Hayata, Atsushi; Tokudome, Nahomi; Akamatsu, Keiichiro; Koh, Yasuhiro; Ueda, Hiroki; Nakanishi, Masanori; Yamamoto, Nobuyuki
Highlights: NSCLC patients treated with immune-checkpoint inhibitors sometimes experience irAEs. Mode of action with immune checkpoint inhibitor suggests that irAEs may correlate with antitumor activity. Nivolumab efficacy among the irAE group was superior to the no-irAE group. Abstract: Objectives: Patients treated with nivolumab often experience its unique adverse events, called immune-related adverse events (irAEs). Regarding the mechanisms of immune-checkpoint inhibitors (ICIs), the occurrence of irAEs may also reflect antitumor responses. Here, we report the clinical correlation between irAEs and efficacy in NSCLC patients treated with nivolumab. Materials and methods: Between December 2015 and February 2017, 38 advanced NSCLC patients were treated in our institution. All the patients were enrolled in our single-institutional, prospective, observational cohort study (UMIN000024414). IrAEs were defined as having a potential immunological basis that required more frequent monitoring and potential intervention. We divided the patients into two groups (irAEs group or no-irAEs group) and evaluated the objective response rate (ORR) and progression-free survival (PFS). Results: The median age of the patients was 68.5 years (range 49–86 years); male/female ratio was 28/10; squamous/non-squamous cell carcinoma cases were 10/28; performance status was 0–1/2/3, 7/26/5. Among the overall population, ORR was 23.7% and median PFS was 91 days. At the data cutoff, 14 irAEs were observed. The most common irAE was interstitial pneumonia (n = 5). Other irAEs were hypothyroidism (n = 4), hyperthyroidism, hypopituitarism, liver dysfunction, rash, and elevated thyroid stimulating hormone levels (n = 1, each). Patients with irAEs had significantly higher ORRs compared with no-irAE patients (63.6% versus 7.4%, p < 0.01). Similarly, the PFS among irAE patients was longer (median: not reached [95% confidence interval CI: 91 days to not applicable]) than no-irAE patients (median 49 days [95% CI: 36–127 days], hazard ratio [HR] 0.10 [95% CI: 0.02–0.37, p < 0.001]). Landmark analysis of patients who achieved PFS ≥60 days demonstrated similar tendencies, but this was not significant (HR 0.28 [95% CI: 0.04–1.46], p = 0.13). Conclusion: There was a correlation between irAE and efficacy in NSCLC patients treated with nivolumab.